The online destination image as portrayed by the user-generated content on social media and its impact on tourists' engagement - Guerreiro, Manuela (2024)
Tourism Destination Image (TDI) is complex, dynamic and multidimensional by nature and shaped by a multitude of events, interactions and sensory impressions, especially once the tourist is at the destination, generating tourists' engagement on social media networks. This study aims to measure the online destination image (ODI) portrayed in user-generated content (UGC) on social media by employing the sentiment analysis method. Data were extracted from Facebook and Instagram on the Visit Algarve social media profile. The Algarve region is situated in the south of Portugal and is one of Europe's most popular tourist destinations. The main results shed light on the relevance of intangible heritage experiences as triggers of positive feelings about the destination. Content shared about tourists' activities in the region generates more engagement in the tourism destination's social media. Tangible heritage received the lowest rated sentiment, and destination agents should strategically look into it as there are opportunities for destination management. Tourism infrastructure has the lowest engagement value; therefore, in terms of promotion, it does not generate interest.